Production of biodegradable plastic by polyhydroxybutyrate (PHB) accumulating bacteria using low cost agricultural waste material - Getachew, Anteneh (BMC Res Notes, 2016)
BACKGROUND: Polyhydroxybutyrates (PHBs) are macromolecules synthesized by bacteria. They are inclusion bodies accumulated as reserve materials when the bacteria grow under different stress conditions. Because of their fast degradability under natural environmental conditions, PHBs are selected as alternatives for production of biodegradable plastics. The aim of this work was to isolate potential PHB producing bacteria, evaluate PHB production using agro-residues as carbon sources. RESULT: Among fifty bacterial strains isolated from different localities, ten PHB accumulating strains were selected and compared for their ability to accumulate PHB granules inside their cells. Isolate Arba Minch Waste Water (AWW) identified as Bacillus spp was found to be the best producer. The optimum pH, temperature, and incubation period for best PHB production by the isolate were 7, 37 °C, and 48 h respectively at 150 rpm. PHB production was best with glucose as carbon source and peptone as nitrogen source. The strain was able to accumulate 55.6, 51.6, 37.4 and 25% PHB when pretreated sugar cane bagasse, corn cob, teff straw (Eragrostis tef) and banana peel were used as carbon sources respectively. Fourier transform-infrared authentication results of the extracted and purified PHB identified its functional units as C–H, CH(2), C=O and C–O groups. UV–Vis spectrophotometric analysis and biodegradability test confirmed the similarity of the extract with standard PHB and its suitability for bioplastic production. CONCLUSION: The isolated Bacillus sp can be used for feasible production of PHB using agro-residues especially sugarcane bagasse which can reduce the production cost in addition to reducing the disposal problem of these substrates. The yield of PHB can further be boosted by optimization of production parameters as substrates.